The impact of rooftop PV and energy storage system on building distribution network - Zhang, Ziwei (2019)
With the evolution of technology day by day, the energy demand is increased accordingly and not to mention the rate of global warming. Recently there has been an increase in the need of exploring renewable energy resources with affordable production and operating costs. Solar energy is considered as one of the main source of energy resources throughout the Earth. Thus is it critical that people understand the technologies within this area of the field. This project is to obtain the impact of rooftop solar PV and energy storage system. While installing PV systems on the rooftop, solar panels face the solar radiations, energy is able to be captured and converted to electricity. This project contains the calculation and analysis of the data before and after installs the rooftop PV system for different loads in different types of buildings. Choose different materials of solar panel will affect the efficiency of solar energy absorbed. Based on the power consumption for different loads in different types of building, able to analyse how much solar energy can reduce consumption. With the solar panels face the solar radiations, energy is able to be captured and converted to electricity and able to store in batteries in order for back up when cloudy days. Therefore, a suitable material of solar panel will improve the efficiency of solar panels in order to decrease the power consumption and reduce the electrical bills.